“We will Manage It” – Did Chancellor Merkel's Dictum Increase or Even Cause the Refugee Movement in 2015? - Ludger Pries (International Migration, 2019)
In public and scientific debates about the dynamics of the so-called refugee crisis of 2015, there are highly controversial positions concerning the statement on August 2015 by Chancellor Merkel: “We will manage it” Did this dictum actually increase or even unleash the refugee migration towards Europe in 2015? Was Germany's governmental policy against the legal European and national frame? Based on an analysis of legal documents and public statements, the article first reconstructs the development of refugee immigration into the EU, especially to Germany, in 2015 and reviews whether the German government violated law and opened one-sided borders. Based on survey data of 4,500 refugees in 2016, it then analyses whether the Merkel dictum significantly changed the volume and the reasons why refugees decided to flee to Germany. Finally, some conclusions are drawn.
Keywords: 300